A Preliminary Assessment on Avian Community in the Urban Forest of Universiti Malaysia Sabah - Lim, Wing-Shen; Andy Russel Mojiol (e-VIBS, Faculty of Science and Natural Resources, 2019)
Preliminary assessment was conducted on avian community that presented at the urban forest of Universiti Malaysia Sabah in present study. Four line transects were established at four randomly-selected locations that surrounded the Forestry Complex in UMS. Point-count survey was employed in sampling avian individuals, and then ancillary data was collected through visual assessment, at each sampling post established along respective transects. A total of 201 avian individuals belonged to 46 species and 23 families were sighted and identified in present study, and then 5 threatened species were encountered at arboretum (Transect 1), stairway (Transect 2) and natural-regenerated forest (Transect 4) habitats. Urban forest habitat of UMS was determined with rich resident avian diversity, especially at the stairway habitat. UMS serves as a shelter to wide range of resident avian species, as well as to several migratory and threatened avian species. Due to small sampling area and short sampling time employed in present study, there is a need to conduct similar study on the entire campus of UMS, to provide a holistic understanding on the relationship between avian community and habitat condition at urban forest ecosystem of UMS, as well as for other urban forests in Kota Kinabalu, Sabah.